Atomic Layer Deposition of NiO on Self‐Supported Co3O4 Nanoneedle Array for Electrocatalytic Methanol Oxidation Reaction. Issue 7 (9th May 2021) - Cheng, Jia; Song, Yanyan; Sun, Mengxiao; Sun, Jiankun; Zhang, Lixue
Abstract : Developing efficient transition metal oxide catalysts is still challenging for direct methanol fuel cells. Herein, an atomic layer deposition method to prepare NiO on a self‐supported Co3 O4 nanoneedle array grown on a porous nickel foam substrate (NiO–Co3 O4 NA@NF) as the electrode for the methanol oxidation reaction (MOR) is reported. The synergistic effect between the NiO and Co3 O4 components as well as the specific 3D nanoarray structure can endow the prepared NiO–Co3 O4 NA@NF with a very promising MOR catalytic activity. As a result, the NiO–Co3 O4 NA@NF catalyst shows a low onset potential (1.27 V vs reversible hydrogen electrode [RHE]), a high current density (173 mA cm −2 @1.524 V vs RHE), and good stability in MOR. This work demonstrates the feasibility of the atomic layer deposition strategy in fabricating complex oxides‐based high‐performance electrocatalysts. Abstract : Herein, an atomic layer deposition strategy to prepare NiO on self‐supported Co3 O4 nanoneedle array grown on porous nickel foam substrate (NiO–Co3 O4 NA@NF) is reported. By virtue of the synergistic effect between NiO and Co3 O4 components as well as the 3D nanoarray structure, the prepared NiO–Co3 O4 NA@NF electrode exhibits a very promising catalytic performance toward the methanol oxidation reaction.